A tudás forradalma. Az internező ember szociálpszichológiája és szociológiája - György Csepeli; Gergő Prazsák (Symbolon, 2020)
The Revolution of Knowledge. The Internet User’s Sociology and Social-Psychology The latest communicational architecture, the internet has not yet a perfectly transparent effect on the entirety of human beings, remodeling and modifying cognition, knowledge, the relationships between people. The network system substantially influences the fields of the social system, listed here politics, economy, culture and the world of life. In this presentation new theories and new research achievements are presented, through these we can understand the new phenomenon of the society moved (migrated) on the internet. A new world has come into existence; its metaphysics is born now.